Survey research on tasks and competencies to inform records management education. (20th March 2017) - Buchanan, Sarah A.; Stratton, Caroline; Sun, Yalin; Chaudhary, Ankita
Abstract : Purpose: The purpose of this paper is to report findings from research conducted to study the everyday work of information professionals, specifically records managers. This paper is a part of the "Research on the Work of 21st Century Information Professionals" study. Design/methodology/approach: Researchers used the tailored design approach to create and increase response rate of our survey. Survey research methodology facilitated the development, pilot and launch of a survey instrument with a 20-question module specific to records management work. Findings: The authors discovered the frequency of 11 tasks in records managers' daily work, as well as how important each of 11 competencies are to their success on the job. Professional development topics and format, job satisfaction, strategies for gaining compliance, desired skills for new hires and curricular recommendations are also presented. Research limitations/implications: The survey generated 334 responses from records management professionals. This sample was based on graduate alumni, targeted professional groups and snowball strategy. Implications from this study include educating doctoral students to study information work and identifying particular areas for strengthening graduate curricula and professional training. Practical implications: The authors obtained direct insight on what records managers do in their daily work that will inform curricular decision-making. Originality/value: The study explores an interest in daily work activities through multiple quantifiable data measures to offer nuanced insight on the relationships between different aspects of records management work.